PENGENALAN STRATEGI PRODUK SEBAGAI UPAYA PENGEMBANGAN BISNIS LTQ UTRUJJAH - Lusianingrum, Farah Putri Wenang (CV Widina Media Utama, 2022)
The transformation of Islamic boarding schools in Indonesia was also carried out by LTQ Utrujjah. LTQ Utrujjah began to carry out entrepreneurial activities by involving all students and their administrators to create independence for LTQ in general and independence for graduates in particular. The business activities carried out by the students and administrators of LTQ Utrujjah before the Covid-19 pandemic were running quite well with the main target consumers being pilgrims visiting LTQ Utrujjah. However, since the Covid-19 pandemic, business activities have been difficult to develop because the products owned by students and administrators are unable to compete with other products when marketed outside LTQ. This condition provides encouragement for the introduction of product strategies to be implemented as an effort to develop the LTQ Utrujjah business. This activity aims to provide an understanding of the importance of product strategy and can then be applied by participants. The method for delivering the material in this activity is with a lecture, discussion and tutorial approach. Activity participants took part in all events enthusiastically and actively. The service activity was successful because the participants were assessed as understanding the product strategy material by showing their activeness in the discussion.ABSTRAKTransformasi Pesantren di Indonesia juga dilakukan oleh LTQ Utrujjah. LTQ Utrujjah mulai untuk melakukan kegiatan kewirausahaan dengan melibatkan seluruh santri beserta pengurusnya untuk menciptakan kemandirian LTQ secara umum dan kemandirian lulusan secara khusus. Kegiatan bisnis yang dilakukan oleh santri dan pengurus LTQ Utrujjah sebelum adanya pandemi Covid-19 cukup berjalan dengan baik dengan sasaran utama konsumennya yaitu jamaah yang berkunjung ke LTQ Utrujjah. Namun, sejak pandemi Covid-19 kegiatan bisnisnya sulit berkembang disebabkan produk-produk yang dimiliki santri dan pengurus kurang mampu bersaing dengan produk lain ketika dipasarkan diluar LTQ. Kondisi ini memberikan dorongan untuk dilaksanakan pengenalan strategi produk sebagai upaya untuk pengembangan bisnis LTQ Utrujjah. Kegiatan ini bertujuan memberikan pemahaman mengenai pentingnya stratagi produk dan selanjutnya akan dapat diaplikasikan oleh peserta. Metode pelaksanaan penyampaian materi pada kegiatan ini dengan pendekatan ceramah, diskusi, dan tutorial. Peserta kegiatan mengikuti seluruh acara dengan semangat dan aktif. Kegiatan pengabdian berhasil sebab peserta dinilai memahami materi strategi produk dengan memperlihatkan keaktifannya dalam diskusi.